Quantum public-key encryption protocol based on single-photon - Wen-jun LUO; Guan-li LIU (Tongxin xuebao)
A quantum public-key encryption protocol based on single-photon was provided.Pseudo random sequence mapping to private keys to implement corresponding quantum operations and then obtaining quantum public-key to encode the plaintext was used.Employ the method of block classification to lower the requirement for storage capacity of the sender.A new quantum source as transmission carrier was introduced and simply encoding and decoding rules were designed based on the laws of quantum non-cloning and ciphertext indistinguishability.On the other hand,classical one-time pad technique is used to ensure the security of quantum key and plaintext in the transmission channel.At the same time,select different updating strategy of quantum public-key according to the results of error detection which can significantly reduce key consumption.Compared with the previous quantum public-key encryption based on entangled states and single-photon,there are no entangled states and decoyed particles are needed,so it is not only efficient to reduce the overhead of communication traffic between legitimate users,but also easier to carry out in practice.The analysis shows that the proposed scheme is secure.